UVEITIS CAUSED BY TREATMENT FOR MALIGNANT MELANOMA: A CASE SERIES. Issue Volume 15:Issues 6(2021) (November 2021) - Whist, Eline; Symes, Richard J.; Chang, John H.; Chowdhury, Vivek; Lim, Li-Anne; Grigg, John R.; Lin, Ming-Lee; Karaconji, Tanya; Giblin, Michael; Symons, Andrew; Lim, Lyndell L.; McCluskey, Peter J.
Abstract : Background/Purpose: To report the largest case series to date of uveitis occurring in association with immunomodulatory therapy for malignant melanoma. Methods: A retrospective multicenter case review. Twenty-two patients with uveitis occurring in association with either immunotherapy or targeted immune therapy for malignant melanoma were identified. Results: Of 22 patients, 11 had anterior uveitis in isolation. The remainder showed a variety of clinical features including panuveitis, ocular hypotony, papillitis, cystoid macular edema, and melanoma-associated retinopathy. Most patients responded well to treatment. Conclusion: We report the largest case series to date of patients with uveitis secondary to drug treatment for malignant melanoma. These cases are likely to increase in number in the future as newer immunomodulatory therapies for cancers are developed and the indications for these drugs increase. A dilemma arises when patients respond well to these drugs but develop vision-threatening side effects. Abstract : Supplemental Digital Content is Available in the Text.The largest case series to date describing uveitis occurring secondary to systemic treatments for malignant melanoma. Twenty-two cases are described. Uveitis occurred after treatment with checkpoint, BRAF, and mitogen-activated protein kinase inhibitors.